Plasma ceramide and phospholipid-based risk score and the risk of cardiovascular death in patients after acute coronary syndrome. (29th December 2020) - Gencer, Baris; Morrow, David A; Braunwald, Eugene; Goodrich, Erica L; Hilvo, Mika; Kauhanen, Dimple; Sabatine, Marc S; Laaksonen, Reijo; O'Donoghue, Michelle L
Abstract: Aims: Ceramide (Cer) and phosphatidylcholine (PC) lipids are associated with pathophysiological processes in cardiovascular (CV) diseases. A previously derived and validated plasma Cer-PC risk score (CERT2) was associated with CV death risk in patients with stable disease, but its prognostic value has not been evaluated in patients early post-acute coronary syndrome (ACS). Methods and results: Prespecified plasma Cer and PC species in the CERT2 risk score were measured in 4871 subjects from SOLID-TIMI 52, which enrolled patients ≤30 days after ACS (median follow-up 2.5 years). The CERT2 score (scale 0–12 points) was calculated as previously defined. The primary outcome was CV death; Coronary heart disease death, all-cause death, hospitalization for heart failure (HF), myocardial infarction (MI) and stroke were also analyzed. Poisson models included baseline characteristics and established biomarkers. Patients with higher CERT2 risk scores were more likely to be older, female, current smokers, presenting with STEMI, and to have impaired renal function and higher LDL-C. After multivariable adjustment, patients in the highest risk score category remained at a nearly two-fold higher risk of CV death (adj relative risk [RR] 1.92, 95% CI 1.01–3.66, P = 0.047). Patients in the highest risk score category were also at higher risk of all-cause death (adj RR 2.01, 95% CI 1.21–3.35, P = 0.007), whereas the relationships with HF, MI, and stroke were attenuated with multivariable adjustment. Conclusions: A plasma ceramide and phospholipid-based risk score is associated with the risk of CV death independent of established clinical risk factors and biomarkers in patients after ACS.